Early Vascular Aging in Children With Tuberous Sclerosis Complex - Skrzypczyk, Piotr; Wabik, Anna Maria; Szyszka, Michał; Józwiak, Sergiusz; Bombiński, Przemysław; Jakimów-Kostrzewa, Aleksandra; Brzewski, Michał; Pańczyk-Tomaszewska, Małgorzata (Frontiers in Pediatrics, 2021)
Objectives: Experimental data indicate that activating mutations in the mTOR (mammalian target of rapamycin) pathway may lead to abnormal arterial wall structure. Vascular anomalies like arterial stenoses are reported in pediatric patients with tuberous sclerosis complex (TSC). In addition, large renal lesions (angiomyolipoma – AML and cysts) are risk factors for arterial hypertension in adult patients with TSC. This study aimed to assess blood pressure, including central blood pressure and arterial damage (early vascular aging – EVA) in children with TSC. Material and methods: In a group of 33 pediatric patients with TSC (11.13±4.03 years, 15 boys, 18 girls), we evaluated peripheral and central office blood pressure, 24-hour ambulatory blood pressure, and arterial damage: aortic pulse wave velocity (aPWV) [m/s], [Z-score], augmentation index (AIx75HR [%]), common carotid artery intima-media thickness (cIMT) [mm], [Z-score], stiffness of common carotid artery (E-tracking), renal lesions in magnetic resonance and ultrasonography, and selected biochemical parameters. The control group consisted of 33 healthy children (11.23±3.28 years, 15 boys, 18 girls). Results: In TSC group 7 (21.2%) children had arterial hypertension, 27 (81.8%) children had renal angiomyolipomas, 26 (78.8%) - renal cysts, and 4 (12.1%) patients were treated with mTOR inhibitors (2 patients with everolimus and 2 patients with sirolimus) at the moment of evaluation. Children with TSC had higher central systolic blood pressure (AoSBP) (98.63±9.65 vs. 90.45±6.87 [mm Hg], p<0.001), cIMT (0.42±0.05 vs. 0.39±0.03 [mm], p=0.011), cIMT Z-score (0.81±1.21 vs. 0.16±0.57, p=0.007), aPWV (4.78±0.81 vs. 4.25±0.56 [m/s], p=0.003) and aPWV Z-score (-0.14±1.15 vs. -0.96±0.87, p=0.002) compared to healthy children, without differences in AIx75HR (8.71±15.90 vs. 5.24±11.12 [%], p=0.319) and stiffness of common carotid artery. In children with TSC AoSBP correlated positively with serum cystatin C concentration (r=0.377, p=0.030) and with maximum diameter of renal cyst (r=0.419, p=0.033); mean arterial pressure (MAP) 24h Z-score correlated with serum cystatin C concentration (r=0.433, p=0.013); and aPWV Z-score with daily urinary albumin loss [mg/24h] (r=0.412, p=0.029). Conclusions: Children with tuberous sclerosis complex are at risk of elevated central blood pressure and early vascular aging. In children with TSC, blood pressure and arterial stiffness are related to renal involvement.